HUBUNGAN ANTARA PERSEPSI ORANG TUA TERHADAP KEMAMPUAN ANAK DAN DUKUNGAN SOSIAL DENGAN PENERIMAAN ORANGTUA PADA ANAK CEREBAL PALSY DI YPAC SE-JAWA TIMUR - Taty Arnita Panjaitan; Wiwik Sulistiani; Weni Endahing Warni (Fakultas Psikologi Universitas Hang Tuah, 2018)
Parents who had special dissability child especially cerebral palsy should have positive attitude to the child, so the child could grow optimally. Parents perception to child ability and social support that the parents receive will affect the parents in accepting the child. The aim of this research is to find out the correlation between parents perception towards the child ability and social support with parents acceptance to cerebral palsy child in East Java YPAC. The sample of this research is parents who had cerebral palsy child in East Java YPAC with total data received fifty-three parents. The technique of the data collection use a likert scale. Based on the data analysis result between parents perception towards the child ability and social support with parents acceptance to cerebral palsy child in East Java YPAC result the r 0, 528 to significance level (p) 0,000 (p is less than 0,05). So the submitted hypothesis mention that there is correlation between parents perception towards the child ability and social support with parents acceptance to cerebral palsy child in East Java YPAC is accepted.